Synthesis and Application of Acylhydrazone Probe with High Selectivity and Rapid Detection of Mercury Ion. Issue 1 (2nd January 2023) - Shi, Tianzhu; Xie, Zhengfeng; He, Jiawei; Wu, Fuyong; Li, Honghe; Guo, Ju; Zhao, Jingjing
Abstract: A Schiff base acylhydrazone fluorescent probe (DPTYMH) was designed and synthesized using 3‐bromo‐N, N‐diphenylaniline, 5‐formyl‐2‐thiopheneboronic acid, and 2‐hydroxybenzohydrazide. The structure was then verified by 1 H NMR, 13 C NMR and HR‐MS. DPTYMH exhibited positive solvent photochromic effect based on the mechanism of intra‐molecular charge transfer (ICT), and demonstrated effectiveness, high selectivity, and specificity to capture mercury ion (Hg 2+ ). The response time and the detection limit of DPTYMH on Hg 2+ was under 10 s and as low as 1.01×10 −8  M, respectively. Density Functional Theory (DFT) calculation and 1 H NMR were used to investigate the potential coordination mechanism. The Hg 2+ level of several water samples had been effectively analyzed using DPTYMH. The molecular logic gate was also built using Hg 2+ and EDTA as chemical inputs by taking use of DPTYMH′s reversibility in the presence of EDTA. Moreover, the DPTYMH was produced as test strips, which has the enormous potential to detect Hg 2+ ions in the environment. Abstract : The aromatic aldehyde salicylylhydrazone fluorescent probe molecule DPTYMH was prepared, which can recognize Hg 2+ ions with high selectivity and sensitivity, and the detection limit is 1.01×10 −8  M. Moreover, the DPTYMH was produced as test strips, which has the enormous potential to detect Hg 2+ ions in the environment under natural light and 365 nm UV light.